Embracing Diversity, Equity, and Inclusion in the Scientific Community—Viewpoints of the Diversity, Equity, and Inclusion Committee of the North American Vascular Biology Organization - Garelnabi, Mahdi; Cowdin, Mitzy; Fang, Yun; Shrestha, Bandana; Ushio-Fukai, Masuko; Aikawa, Elena; Graham, Garth; Molema, Grietje; Yanagisawa, Hiromi; Aikawa, Masanori (Frontiers in Cardiovascular Medicine, 2022)
Recent increased visibility on racial issues in the United States elicited public outcry and a collective call for action. The social justice movement has facilitated energetic discussions about race, sexual orientation, and various issues of diversity, equity, and inclusion. This article discusses issues faced by people of color that we as scientists can address, as well as challenges faced by women and internationally trained scientists in the scientific community that need immediate attention. Moreover, we highlight various ways to resolve such issues at both institutional and individual levels. Silence and incremental solutions are no longer acceptable to achieving lasting social justice and ensure prosperous societies that work for all.